As blusas verdes e as marchadeiras. Movimentos de mulheres e participação politica nos anos 30 e 60 - Possas, Lidia Maria Vianna [UNESP] (My University, 2012)
Understanding the women’s political manifest at the present national scenario through analyzing the historicity and complexity of women’s movement and their contradictions regarding females / feminists actions in public and political areas. Thus, I give emphasis to the 30s and its “green blouses” and 60’s with “the marchadeiras” showing how those conservatives movements and their facist trend took on organized actions. And, also acting on the opposite way of democratic areas and the struggles for increasing the rights and advocating the maintenance of a status quo, keeping female traditional practices. Those women, who were living in the most visible female conjunctures and resistance to authoritarian governments, have taken positions that were holding back the progress in the game, contributing to reflux before the conquest of rights and gender equity.

Compreender as manifestações políticas das mulheres no atual cenário nacional analisando a historicidade e complexidade dos movimento de mulheres, suas contradições frente às ações femininas/feministas no espaço publico e político. Para tanto pontuo os anos 30, com as “blusas verdes” e 60 com as “marchadeiras” evidenciando como esses movimentos de natureza conservadores e de tendências fascistas assumiram ações organizadas e agindo na contra mão dos espaços democráticos e das lutas pela ampliação de diretos e de participação política defendendo a manutenção de um status quo, das permanências de práticas femininas tradicionais. Aquelas mulheres vivendo em conjunturas de maior visibilidade feminina e de resistências aos governos autoritários assumiram posicionamentos refreando os avanços que estavam em jogo, contribuindo para o refluxo diante da conquista de direitos e de equidade de gênero.
The “green blouse”s and the “marchadeiras”. Women’s movement and the political participation in the 1930s and 1960s Brazil
Keywords: Movimentos femininos; Blusas Verdes/Integralistas; Marchadeiras; Participação Politica